Arcing Faults Detection in Switchgear with Extreme Learning Machine - Ishak S.; Koh S.P.; Tan J.D.; Tiong S.K.; Chen C.P.; Yaw C.T. (Institute of Physics, 2023)
Frequency domain analysis; Knowledge acquisition; Time domain analysis; Arcing; Arcing faults; Extreme learning machine; Fault sensing; Faults detection; General efficiencies; Learning machines; Power-distribution system; Switchgear fault; Validation stages; Fault detection